Choledochocele: A Case Report and Discussion of Diagnosis Criteria - Linlin Zhu; Zhibao Lv; Jiangbin Liu; Weijue Xu (Georg Thieme Verlag KG, 2015)
Abstract A 6-year-old girl presented with intermittent abdominal pain, without jaundice and a palpable mass in the epigastrium. Preoperative imaging and upper endoscopy suggested duodenal duplication. During surgery, the patient was diagnosed with a rare type of choledochal cyst-choledochocele (type 3b). The authors emphasize that, in children, choledochocele should be included in the differential diagnosis of cystic lesions located in the duodenal area and the head of the pancreas area, regardless of jaundice or abnormal liver function. Since mucosal histology showing duodenal mucosa did not match the final diagnosis, we suggest that three criteria should be met for the diagnosis of a choledochocele to be diagnosed: (1) a cyst protruding into the duodenal lumen; (2) filling with contrast during cholangiography and (3) a filling defect on X-ray barium meal.